Pengembangan Media Pembelajaran Video Berbasis Animasi pada Pelatihan Pengenalan Produk Bahan Bakar Minyak dan Liquified Petroleum Gas - Eva Khuzaifah (Syntax Corporation Indonesia, 2024)
Digital learning media using animation-based videos can help trainees to understand learning material in accordance with learning objectives. This research uses the ADDIE development model which consists of stages of analysis, planning, development, implementation, and evaluation, and this research only reaches the development stage. Determination of samples using random sampling techniques, and the number of samples was 50 participants. The data obtained in the development of this animated video media was obtained by validating the material and media, as well as seeing the participants' responses to the media developed using participant response questionnaires, scale methods with Likert modifications. The results of expert validation are in the Very Valid category and received a very decent response from participants and it can be stated that the animated video learning media developed is very valid for use in learning.